High‐range‐resolution two‐dimensional imaging using frequency diversity multiple‐input–multiple‐output sonar. Issue 5 (1st June 2016) - Liu, Xionghou; Sun, Chao; Yang, Yixin; Zhuo, Jie
Abstract : A high‐range‐resolution imaging method for a multiple‐input–multiple‐output sonar is proposed. In this method, a set of frequency diversity linear frequency modulation (FD‐LFM) pulses is transmitted, with a zero bandgap between two adjacent FD‐LFM pulses to suppress cross‐correlation functions. At the processing end, the synthesised matched filtering, which combines the matched filtering and the frequency band synthesising into one step, is proposed to reduce the computation burden. Moreover, the frequency‐domain weighting is adopted to suppress to the sidelobes of the synthesised auto‐correlation function to further improve the image quality. The effectiveness of the proposed method is validated via the theoretical analysis, numerical simulations and water tank experiments.